SOCIAL PSYCHOLOGICAL CHARACTERISTICS OF THE CRIMINAL PERSONALITY. - Nuralieva Dildora Mamurjonovna; Z. Ergashova (Scholar Express Journal, 2022)
At the same time that reforms are currently being carried out in the legal sphere, law enforcement agencies set such a responsible task as not to disclose crimes committed in society and not to bring any citizens to justice without Assos. For this purpose, the importance of a good knowledge and study of the personality of the Criminal, his psychological characteristics is highlighted
Keywords: CRIME; crime index; criminal liability; functional